Multilocus Sequencing Typing of Invasive Haemophilus influenzae strains Isolated in Portugal in the Pre-vaccination Period (1989-2001) - Veiga, Elisabete (2016)
Introduction: Haemophilus influenzae can cause life-threatening infections in children and adults, such as pneumonia, bacteremia, and meningitis, despite de availability of the H. influenzae type b vaccine. Six capsular types, a-f, have been identified to date. Non-capsulated (NC) H. influenzae have also been described. Multilocus Sequencing Typing (MLST) is a powerful method that allows a precise and unambiguous characterization of H. influenzae genotypes. Aim: Identification of the major genotypes that characterize Portuguese invasive H. influenzae strains in the years before the implementation of the Hib vaccine (1989-2001). Comparison of results from this study with the ones from our previous published study with isolates from pos-vaccination period (2002-2010). Methods: Seventy invasive H. influenzae strains (38 Hib, 31 NC, 1 f) were randomly selected for analysis, isolated during 1989-2001 from cerebrospinal fluid (n=24), blood (n=43) and pleural fluid (n=3). Thirty-six strains (51.4%) were isolated from pre-school children. Capsular status was identified by PCR amplification of bexA gene and capsular type was determined by amplification of capsule-specific genes (for serotypes a-f) using primers and conditions described in the literature. MLST was performed by sequencing internal fragments of the 7 housekeeping genes (adk, atpG, frdB, fucK, mdh, pgi and recA). Sequences were analyzed and submitted to the MLST website (http://haemophilus.mlst.net) for assignment of the sequence type (ST). Phylogenetic estimations were conducted through MEGA5 by using the neighbor-joining method. Results: Thirty-four (89.5%) of the 38 Hib isolates analyzed were assigned to CC6, 4 of which were new STs, while 4 were single strains of different STs. Of the 31 NC isolates, 26 (83.9%) were single strains of different STs (12 new STs), 4 strains belong to CC395 and CC396 (2 strains each), and 1 was identified as CC6. The isolate type f was characterized as ST124. Discussion and conclusions: In this study we observed a high diversity of NC strains, in opposite to Hib clonality. Despite of the great decline of serotype b in the pos-vaccination period, with a concomitant increase of NC and non–b isolates, no significant differences were observed in the MLST characterization of pre-vaccination isolates. Of the 16 Hib studied, all but one were characterized as CC6 (94.7%). Among the 67 NC isolates, 42 (62.7%) were single strains of different STs; the remaining isolates were of 6 different CCs. In conclusion, there are no differences in molecular typing of H. influenzae strains isolated in the pre and pos-vaccination period, in our country. The majority of episodes of invasive disease occurring in Portugal are now due to fully susceptible, highly diverse, non-capsulated strains. Given the evolving dynamics of this pathogen and the increase in non-type b capsulated isolates, continuous surveillance is needed.